Human capital metrics: a critical decision point during the merger and acquisition process - Bruehlman, August P., author; Geroy, Gary D., advisor; Banning, James H., committee member; McCambridge, James A., committee member; Morgan, George A., committee member (Colorado State University. Libraries, 2005)
This study examines the importance of human capital during the merger and acquisition (M&A) process. M&A has become a commonplace strategy in the global business world of the 21st century. Approximately 50% of attempted mergers fail to live up to management's financial expectations. Post-mortems of failed integrations suggest that the human component is often a leading cause of failure and the deleterious effects on stakeholders. A prescriptive research method was designed within the quantitative paradigm that used a secure web format to administer an original merger and acquisitions survey instrument (MASI) to a group of 312 masters' level business and human resources students. The MASI gathered responses on a 7 point rating scale to variables in three general areas: the M&A decision process, identifiable human capital factors, and measurable human capital manifestations. Data were analyzed using t tests, pairwise t tests, repeated measures ANOVAs, and qualitative coding processes on two open ended responses. Findings from the data suggested that management effectiveness, culture, and human capital valuation are the three most critical decision points to focus on during the merger and acquisition process. Human resources and other business participants significantly differed on only 4 of the 19 variables: regulatory compliance and employee demographics in the identifiable factors group; and human capital valuation and employee contracts/unionization in the measurable manifestations group. No significant differences were found between participants who had experienced successful or unsuccessful M&As. This study is significant in four overarching ways: 1. An original survey (MASI) was created to research 19 variables suggested by the literature. 2. Of the 19 variables, one in each group was rated significantly higher than most others by survey participants: management effectiveness, culture and human capital valuation. 3. The study suggests that there are significant differences in the viewpoints of human resources and other business management regarding the M&A process within two of the identifiable factors and two measurable manifestations–but not within the decision making group. 4. The study also suggests that there are no significant differences in the viewpoints of participants who are successful or unsuccessful in their M&A experiences.
Keywords: studies; polls and surveys; research; statistical data; investments; success; trends; divorce; data analysis; knowledge; decision making; copyright; attitudes